2018
DOI: 10.1186/s12951-018-0388-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting extracellular vesicles to injured tissue using membrane cloaking and surface display

Abstract: BackgroundExtracellular vesicles (EVs) and exosomes are nano-sized, membrane-bound vesicles shed by most eukaryotic cells studied to date. EVs play key signaling roles in cellular development, cancer metastasis, immune modulation and tissue regeneration. Attempts to modify exosomes to increase their targeting efficiency to specific tissue types are still in their infancy. Here we describe an EV membrane anchoring platform termed “cloaking” to directly embed tissue-specific antibodies or homing peptides on EV m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
129
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(147 citation statements)
references
References 79 publications
0
129
0
Order By: Relevance
“…In addition to natural cell-targeting abilities, it is also possible to engineer exosomes to target specific tissues or cells [102]. PEGylation of exosomes resulted in targeted accumulation of exosomes derived from cardiosphere-derived cells in ischemic myocardium in mice [111]. Targeted delivery of exosomes by genetic modification of their surface proteins has been also been reported: (1) brain targeting by rabies viral glycoprotein (RVG) peptide or RGD motif [19,112]; and (2) tumor targeting by EGFR-specific nanobodies or HER2-specific single-chain variable fragments [113].…”
Section: Tissue Targeting By Exosome Engineeringmentioning
confidence: 99%
“…In addition to natural cell-targeting abilities, it is also possible to engineer exosomes to target specific tissues or cells [102]. PEGylation of exosomes resulted in targeted accumulation of exosomes derived from cardiosphere-derived cells in ischemic myocardium in mice [111]. Targeted delivery of exosomes by genetic modification of their surface proteins has been also been reported: (1) brain targeting by rabies viral glycoprotein (RVG) peptide or RGD motif [19,112]; and (2) tumor targeting by EGFR-specific nanobodies or HER2-specific single-chain variable fragments [113].…”
Section: Tissue Targeting By Exosome Engineeringmentioning
confidence: 99%
“…Our study highlights the role of myocyte remodelling for both the triggers and functional substrate of the arrhythmia. Therefore, targeting the myocytes through local approaches such as targeted gene therapy (Sasano et al 2006) and exosome targeting (Antes et al 2018) may offer alternative, non-destructive strategies to treat post-MI arrhythmia.…”
Section: Implications For Arrhythmogenesis and Therapymentioning
confidence: 99%
“…Several studies have been lately reported suggesting alternative strategies to functionalise EVs for more accurate targeting of the damaged heart [220,221]. These include: lentiviral vector-based engineering of secreting cells to upregulate the expression of cardiomyocyte-specific binding peptides fused to the murine transmembrane protein Lamp2b, in order to enrich the targeting epitope on the exosomal surface [222]; overexpression of exosomal CXCR4 to push their bioavailability towards the ischaemic heart [156]; membrane anchoring systems to directly dock tissue-specific antibodies or homing antigens on the EV surface [223,224].…”
Section: Looking For the Right Address: Improving Ev Cardiac Tropismmentioning
confidence: 99%